PENGARUH PROMOSI, FASHION INVOLVEMENT, DAN SHOPPING LIFE STYLE, DAN IMPULSE BUYING DI E-COMMERCE SHOPEE - Alimul Kabir Albant; Muhammad Rizki Maulana Putra; Laeli Novita Sari; Vicky F Sanjaya (Journal of Islamic Economy and Business (JIsEB), 2024)
The purpose of this study was to see the effect of Sales Promotion / Promotion, Fashion engagement, and Shopping lifestyle on Impulse Buying in an E-Commerce shopee. This study uses quantitative methods in this study. data through a questionnaire distributed to respondents via social media. The sample in this study were users and consumers of Shopee with a total of 64 respondents. The statistical test was carried out with PLS-based Structural Equation Modeling. The validity test uses the factor loading value, while the reliability is tested using the Cronbach alpha value, composite reliability, and Average Variance Extracted (AVE). After the overall results of the indicator items used are valid, and also reliable, then a Hypothesis Test is carried out. Of the three proposed hypotheses, only one hypothesis is not supported, and two other hypotheses are supported. Based on the results of the study, it was found that Sales Promotion had a negative effect on Impulse Buying, Fashion Involvement had a positive effect on Impulse Buying, and Shopping Life Style had a positive effect on Impulse Buying in E-Commerce Shopee.